Comparison of Alignment Efficiency of Steel Versus Elastomeric Ligatures in Lower Anterior Teeth: A Randomized Clinical Trial: Comparing Ligatures for Orthodontic Alignment - Javaid, Aatikah; Gul, Palwasha (Pakistan Journal of Health Sciences, 2025)
Ligature type influences orthodontic treatment speed, but conclusive evidence comparing alignment time between steel and elastomeric ligatures is limited. Objective: To compare the treatment time required by elastomeric ligatures and steel ligatures, in days, to achieve complete alignment of the lower anterior teeth. Methods: This randomized clinical trial was conducted at Khyber College of Dentistry, Peshawar, involving 180 participants (90 in each group: steel and elastomeric ligatures). The study included patients aged 12 to 18 years undergoing fixed orthodontic treatment with lower premolar extractions and a Little's Irregularity Index of 3-9 mm. Exclusion criteria included systemic conditions, specific dental conditions, and poor periodontal health. Participants were randomly assigned to either the steel or elastomeric ligature group, and the time to reach alignment in the lower arch was recorded. A Student's t-test was used for comparison. Results: The age (p = 0.86), gender distribution (p = 0.21), and age groups (p = 0.73) were similar across both groups. The steel ligature group required less time (218.39 ± 10.02 days) compared to the elastomeric group (224.64 ± 9.39 days) (p < 0.001). This trend was consistent across gender, with both females and males showing significant differences (p < 0.001 and p = 0.004, respectively). The 12–15 years age group also showed a significant difference (p < 0.001), while the 16–18 years group demonstrated a smaller but still significant difference (p = 0.016). Conclusion: Stainless steel ligatures required less time to achieve optimal alignment.